Systemic Lupus Erythematosus and Autoimmune Hepatitis: A Case Report: Lúpus Eritematoso Sistémico e Hepatite Autoimune: A Propósito de um Caso Clínico - Albuquerque, Margarida; Sousa, Maria José; Ribeiro, Rita; Menezes, Maria; Sousa, José Germano de; Sousa, Germano de (Gazeta Médica, 2017)
Systemic lupus erythematosus is a multisystem autoimmune disorder. Liver involvement is normally not a part of the systemic lupus erythematosus spectrum, but is seen in up to 60% of patients. The clinical presentation of autoimmune hepatitis ranges from asymptomatic disease, recognized only by incidentally biochemical abnormalities, to an acute or even fulminant hepatitis. It is important to distinguish systemic lupus erythematosus associated hepatitis from autoimmune hepatitis since complications and therapies are different in the two conditions. The co-occurrence of systemic lupus erythematosus and autoimmune hepatitis is rare, and few cases are reported in the literature so far. The authors present a case report of a 30-year-old female patient from Angola, diagnosed for systemic lupus erythematosus in 2005 in immunosuppressive therapy for almost 10 years with methotrexate and cyclosporine. In 2014, she presents recent aggravating complaints for knee and elbow arthralgia, with morning rigidity over 2 hours, abdominal pain with episodic fever and fatigue are described. In a recent laboratory test evaluation, besides the homogeneous antinuclear antibodies pattern with rising titers, we found a citoplasmatic filamentous pattern suggestive of anti-smooth muscle antibodies found to be F-actine antibodies confirmed in VSM 47 transfected cells that with borderline liver function tests made de diagnosis of autoimune hepatitis in a patient with previous systemic lupus erythematosus. Received: 09/12/2016 - Accepted: 25/05/2017